Antioxidant Properties and Cytotoxic Activity of Ethyl Acetate Fraction of Plectranthus amboinicus (Lour.) Spreng. Leaves on HeLa and T47D Cell Lines - Poppy Anjelisa Zaitun Hasibuan; Panal Sitorus; Denny Satria; Rizka Damela Sibuea (Indonesian Society for Cancer Chemoprevention, 2019)
Research into plants with anticancer effects is actively encouraged in orderto discover new drugs with lessertoxicity but more potent effects. The aims of study are to evaluate the antioxidant properties and to investigate the cytotoxic activity of Plectranthus amboinicus (Lour.) Spreng. leaves ethyl acetate fractions on HeLa,T47D and MCF7 cell lines. The extract was prepared by graded maceration using n-hexane and ethyl acetate. The ethyl acetate extract was fractionated in vacuum liquid chromatography with n-hexane: ethyl acetate; and ethyl acetate: methanol as mobile phase. Then, the fractions were analyzed with thin layer chromatography (TLC). The free radical scavenging activity was measured by DPPH method, the total flavonoid content was calculated by quercetin equivalent and the absorbance is measured by using UV-Visible spectrophotometry. The cytotoxic activity were determined using MTT assay. The fractions contained 5 sub fractions with same TLC profile. The fractions showed antioxidant activity by DPPH method with different IC50 values, namely: 130 µg/mL(I), 127 µg/mL(II), 137 µg/mL(III), 129 µg/mL(IV), and 124 µg/ mL(V), respectively. The measurement of total flavonoid content showed 118 mg QE/g (I), 50 mg QE/g (II), 207 mg QE/g (III), 56 mg QE/g (IV), and 55 mg QE/g (V). The IC50 of each sub fractions on HeLa cell were 77 µg/mL, 46 µg/mL, 93 µg/mL, 71 µg/mL and 476 µg/mL; for T47D cell were 1621 µg/mL, 111 µg/mL, 128 µg/mL, 150 µg/mL and 209 µg/mL; and for MCF7 were 259 µg/mL, 343 µg/mL, 575 µg/mL, 408 µg/mL and 250 µg/mL. Based on the results, the fractions derived from ethyl acetate extract of Plectranthus amboinicus (Lour.) Spreng. leaves exhibit antioxidant. The Fraction II from ethyl acetate extract of Plectranthus amboinicus (Lour.) Spreng. was the most cytotoxic on HeLa, T47D and MCF7 cell lines. It is potential to undergo further isolation of its cytotoxic compounds.Keywords : antioxidant, cytotoxic, Plectranthus amboinicul (Lour.) Spreng., ethyl acetate fractions